A combined experimental and computational study on the oxidative degradation of bromophenols by Fe(VI) and the formation of self-coupling products. (March 2020) - Dar, Afzal Ahmed; Chen, Jing; Shad, Asam; Pan, Xiaoxue; Yao, Jiayi; Bin-Jumah, May; Allam, Ahmed A.; Huo, Zongli; Zhu, Feng; Wang, Zunyao
Abstract: In this study, the degradation of eight bromophenols (BPs), including monobromophenols (2-BP, 3-BP, and 4-BP), dibromophenols (2, 4-DBP, 2, 6-DBP, and 3, 5-DBP), a tribromophenol (2, 4, 6-TBP) and a pentabromophenol (PBP), by a Fe(VI) reaction process at a pH of 8.0 was systematically studied. It was concluded that their degradation rates increased with increasing Fe(VI) concentrations in solution. The removal of 2, 4, 6-TBP, 2-BP, and 2, 6-DBP was faster than that of the other five BPs, which could be attributed to the position of the substituting Br atom. Moreover, the direct oxidation and coupling reactions greatly influenced the reactivity of the bromophenols with Fe(VI). The electron paramagnetic resonance (EPR) analysis confirmed the presence of hydroxyl radicals in present system. The oxidation reaction products of PBP and 2-BP were recognized by an electrospray time-of-flight mass spectrometer; hydroxylation, hydroxyl substitution, the cleavage of the C–C bond, direct oxidation and polymerization via an end linking mechanism were noticeably found in the reaction process, resulting in the formation of polymerization products and causing hydroxylation to occur. Theoretical calculations further determined the possible oxidation sites of 2-BP and PBP. This study may provide comprehensive and important information on the remediation of BPs by Fe(VI). Graphical abstract: Image 1 Highlights: The degradation processes of eight bromophenols by Fe(VI) were systematically studied. 2-BP, 2, 6-DBP, and 2, 4, 6-TBP were more quickly to be degraded than other five BPs. Six and eleven products were proposed for 2-BP and PBP, respectively. Density functional theory was employed to determine the reaction sites of BPs. Abstract : We systematically studied the degradation kinetics and reaction mechanisms of eight BPs in Fe(VI) reaction process at pH 8.0.